Determination of antiviral activity and cytotoxicity of selected sage (Salvia L.) species - Özçelik, Berrin; Orhan, I. E.; Kan, Yüksel (My University, 2011)
The objective of this study was to examine antiviral property and cytotoxicity of the extracts prepared from the selected Salvia species (Lamiaceae) growing in Turkey. The chloroform and methanol extracts from 14 Salvia species (S. albimaculata, S. aucheri var. canescens, S. candidissima subsp. occidentalis, S. ceratophylla, S. cryptantha, S. cyanescens, S. frigida, S. forskahlei, S. halophila, S. migrostegia, S. multicaulis, S. sclarea, S. syriaca, and S. verticillata subsp. amasiaca) were tested against Herpes simplex (type-1, HSV-1) and Parainfluenza (type-3, PI-3) using Madin-Darby Bovine Kidney and Vero cell lines. Cytotoxicity of the extracts was determined as maximum non-toxic concentrations (MNTCs). The chloroform extracts of S. cyanescens and S. microstegia were found to inhibit both HSV-1 and PI-3 effectively. Therefore, these species could proceed to further evaluation for their possible antiviral components.
Keywords: Antiviral activity; Cytotoxicity; Lamiaceae; Salvia